2022
DOI: 10.1111/hiv.13235
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on HIV testing in the UK’s first Fast‐Track HIV city

Abstract: Objectives: To describe the impact that the COVID-19 pandemic has had on HIV testing in Brighton and Hove, United Kingdom. Methods:All HIV tests performed in Brighton and Hove from January 2016 to June 2021 were extracted, de-duplicated and anonymized. Analysis was performed to compare the monthly numbers of tests and diagnoses before and during the pandemic across different services. Results:The number of patients having tests for HIV in sexual health services (SHS) decreased by 64% in April 2020, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A study performed in Brighton (UK) have shown that by June 2021 testing had still not returned to normal across the city. 32 A new analysis on new data collected is planned and will allow to check if testing had recovered the numbers of before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in Brighton (UK) have shown that by June 2021 testing had still not returned to normal across the city. 32 A new analysis on new data collected is planned and will allow to check if testing had recovered the numbers of before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…With data from 225 HIV treatment sites across 42 countries at the end of the first year of the COVID-19 pandemic, this study found that most had experienced disruptions in clinic operations and in the provision of HIV care. Such disruptions were reported by sites across high-, medium-and low-HIV prevalence settings and country income levels, reinforcing concerns raised by modelling studies [9,[11][12][13] and observational research [41][42][43][44][45][46][47][48][49] about the potential of COVID-19 to reverse progress towards 95-95-95 UNAIDS targets to end the HIV epidemic, particularly in settings with a high HIV burden [50].…”
Section: Discussionmentioning
confidence: 99%
“…While clinics in high-prevalence settings were less http://onlinelibrary.wiley.com/doi/10.1002/jia2.26036/full | https://doi.org/10.1002/jia2.26036 likely to report suspending HIV services and appointments, other care-seeking barriers (e.g. lockdown restrictions, transportation and financial barriers, and concerns about COVID-19 exposure) may have presented insurmountable obstacles for patients in these settings, and early data from diverse settings have highlighted sharp decreases in healthcare-seeking for HIV-related services early in the pandemic, including HIV prevention [49,53], diagnosis [24,41,42,[44][45][46][47][48][53][54][55] and treatment [24,43,44,53,55,56], as well as diagnostics and treatment for other infectious diseases and chronic conditions [55][56][57][58]. While some studies in sub-Saharan Africa have reported rebounds in HIV testing and ART initiation [24,59], our findings related to stockouts of second-and third-line ART regimens in high-prevalence and low/lower-income settings are concerning, as the lack of such essential medicines may result in setbacks for both HIV treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-seven documents were included in our study. Seventeen papers [ 25 , 34 – 49 ] were included in the meta-analysis related to HIV testing, see Supplementary Table 2. For the meta-synthesis related to HIV service adaptations, 20 papers [ 50 69 ] were included, see Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%